2018
DOI: 10.1109/jphot.2018.2849884
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Self-Injection Locked Visible Laser Diodes for High Bit-Rate Visible Light Communication

Abstract: We report on self-injection locking in InGaN/GaN (blue/green) and InGaP/AlGaInP (red) visible-light laser diodes. The free-space optical feedback path was accomplished via an external mirror. The effect of injection current, optical power injection ratio, and external cavity length on the spectral linewidth and modulation bandwidth of the lasers is investigated. Our results show that the laser performance was substantially improved. In particular, we achieved a significant increase of ∼57% (1.53-2.41 GHz) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 24 publications
3
19
0
Order By: Relevance
“…Thus, allowing this locked mode to reach lasing condition earlier than the other modes, and hence dominates by suppressing all the adjacent modes. This phenomenon leads to the enhancement in ∆λ, SMSR of the dominant mode, and, consequently, the spectral purity of the laser with reduced amplified spontaneous emission (ASE) noise and high SNR [12] [13]. Moreover, altering the external cavity with solutions to any LD mode could be attained, thus tuning the locked mode wavelength within the gain profile of the LD active region.…”
Section: Theoretical Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, allowing this locked mode to reach lasing condition earlier than the other modes, and hence dominates by suppressing all the adjacent modes. This phenomenon leads to the enhancement in ∆λ, SMSR of the dominant mode, and, consequently, the spectral purity of the laser with reduced amplified spontaneous emission (ASE) noise and high SNR [12] [13]. Moreover, altering the external cavity with solutions to any LD mode could be attained, thus tuning the locked mode wavelength within the gain profile of the LD active region.…”
Section: Theoretical Discussionmentioning
confidence: 99%
“…2(a) demonstrating a significant improvement by ~3.0, ~16.5, and ~3.1 times in ∆λ, SMSR, and the peak power, respectively. Thanks to the SIL scheme that enabled this profound improvement besides improving the modulation bandwidth and the noise of the LD [12] [13]. The tunability of the system is accessed at three injection currents of 21 (~1.0I th ), 42 (~2.0I th ), and 63 mA (~3.0I th ), and two distinct temperatures of 20 (room temperature) and 40 o C. A continuous wavelength tuning of the locked modes satisfying Eqn.…”
Section: Wavelength Tunability Characterizationmentioning
confidence: 99%
“…The slow rise-time of current lighting LEDs is a key factor that limits the VLC throughput; commonly used commercial devices have a 3dB bandwidth of a few tens of MHz [65,66]. Laser diodes have recently been proposed as light sources for VLC systems due to their large bandwidths [67][68][69]. However, laser diodes require considerable diffusing; otherwise, they can only provide a limited illumination coverage that is not suitable for regular lighting facilities.…”
Section: Vlc Transmittermentioning
confidence: 99%
“…A high power GaN laser diode with output power over 7W was reported in [48]. The modulation characteristics of GaN-based laser diodes were studied in various works for VLC and UWOC applications [49][50][51][52][53][54][55]. A 1 GHz modulation bandwidth was measured in a commercial high power blue laser diode [55] and a later study suggested the modulation bandwidth for GaN-based violet laser could reach beyond 5 GHz [56].…”
Section: Gan Based Eeld Sld and Vcselmentioning
confidence: 99%
“…A 1 GHz modulation bandwidth was measured in a commercial high power blue laser diode [55] and a later study suggested the modulation bandwidth for GaN-based violet laser could reach beyond 5 GHz [56]. Utilizing the injection locking technique, it has been reported that the bandwidth of the laser diode can be enhanced, making it promising for high data rate VLC systems [50].…”
Section: Gan Based Eeld Sld and Vcselmentioning
confidence: 99%